(untitled) (Journal of Hama University, 2021)
The study aimed to know the degree of participation of the employees in the Directorate of Education in Damascus governorate in educational decision-making from the point of view of its employees in accordance with the variables ( Gender, years of service، scientific qualification). The study followed the descriptive analytical curriculum and the sample of the study consisted of 360 workers in the Directorate of Education. The resolution was used to collect data and consisted of 28 items. The study reached a set of results, the most important of which are: - There are statistically significant differences between the averages of the respondents to the questionnaire of the degrees of participation in decision-making due to the gender variable in favor of males. - There are statistically significant differences between the averages of respondents to the questionnaire of the degrees of participation in decision-making due to the change in years of experience in favor of more than 10 years. - There are statistically significant differences between the averages of respondents to the questionnaire of the degrees of participation in decision-making due to the change in scientific qualification in favor of graduate studies.